Bridges to affordability: adopting a university OAER mandate with local implementation. Issue 3 (6th July 2020) - Riehman-Murphy, Christina; Raish, Victoria; Mross, Emily; Pritt, Andrea; Nelson, Elizabeth
Abstract : Purpose: This paper aims to describe a case study of the open and affordable educational resources (OAER) initiatives led by Penn State University Libraries (UL) and implemented at its many campuses which are designed to address the challenges students experience accessing and funding their course materials. Design/methodology/approach: This case study will show how a broad administrative mandate for high-level OAER initiatives created the environment for Penn State (PSU) to evolve from individual pioneering units into coordinated university-wide initiatives. This shift, spearheaded by administration with strong UL involvement, allowed for customized and targeted initiatives at its many campuses. By using UL's centralized, but geographically dispersed, structure, library faculty and staff have been supported in their efforts to expand OAER from the ground up to meet individual contexts and campus needs. Findings: As a result of its many open and affordable initiatives, PSUL has been able to demonstrate both savings and increased access for students across PSU's many campuses and World Campus. Broad administrative support has created an environment which enabled UL faculty and staff to lead various initiatives. Originality/value: UL has long been a leader and partner in open and affordability initiatives at PSU because of its core mission of providing access. By sharing the processes and logistics of how a large research institution with many campuses of various sizes implemented a wide variety of library-driven open and affordability initiatives through a centralized but geographically dispersed structure, academic libraries will be able to replicate similar initiatives in their unique contexts.